28‐1: Invited Paper: Bottom‐Up OLED Development by Virtual Design: Systematic Elimination of Performance Bottlenecks Using a Microscopic Simulation Approach. Issue 1 (28th June 2022) - Neumann, Tobias; Symalla, Franz; Strunk, Timo; Feidai, Artem; Kaiser, Simon; Friederich, Pascal; Wenzel, Wolfgang
Abstract : The gap between computational chemistry and parametric device simulations limits the potentially immense impact of computer models on OLED R&D. We present a review on a bottom‐up multiscale modeling approach to bridge this gap and systematically eliminate performance bottlenecks by virtual design. In several case studies we demonstrate how microscopic simulations can support experimental R&D by identifying fundamental reasons for performance bottlenecks, and by deriving strategies for their elimination.